PRINCIPLES OF THE FORMATION OF MATHEMATICAL REPRESENTATIONS IN PRESCHOOL CHILDREN - Toshmatova Zamiraxon Jumanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the principles of the formation of mathematical representations in preschool children.